What is the reproductive number of yellow fever? - Liu, Ying; Rocklöv, Joacim (Journal of travel medicine, 2020)
Yellow fever is a viral vector-borne disease caused by the yellow fever virus with its geographic distribution currently limited to sub-Saharan Africa and South America. The case fatality rate of hospitalized severe yellow fever is above 40%.1The basic reproductive number, R0, can be used to characterize the epidemic potential of a pathogen by assessing the number of secondary cases that would be generated by one infectious case if it was to be introduced into an immunologically naïve population. R0 values that are larger than 1 indicate epidemic growth; values around 1 represent endemicity and for values below 1, the outbreak is declining and the number of new infections will be decreasing in subsequent generations. We conducted a review of published peer-reviewed literature on the estimates of the basic reproductive number of yellow fever and discuss the implications for herd immunity in relation to the critical vaccination levels.
Gesehen am 18.01.2021